PNEUMATIC TUBE TERHADAP DARAH RUTIN DAN LAKTAT DEHIDROGENASE - Liong Boy Kurniawan; Asvin Nurulita; Uleng Bahrun (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
The transportation of laboratorial samples with pneumatic tube system spends less time than when were handled by courier.Pneumatic tube system produces minor vibrations on sample due to the velocity changes during transportation and may cause changeson the blood cells and haemolysis. The aim of this study is to know the effect of sample transportation with pneumatic tube on bloodcells and its effect on hemolysis. A cross sectional study was performed at Dr. Wahidin Sudirohusodo Hospital, Makassar in July 2013.Routine blood, electrolyte and LDH were tested in 12 out-patients. The researchers collected two (2) samples, for each EDTA tube (routineblood tests) and serum (electrolyte and LDH). The samples were transported using pneumatic tube and the paired samples were sentby courier. The result then were analyzed with Paired T-Test. There were no significant difference of routine blood test results betweensamples sent by pneumatic tube and courier except RDW. RDW were higher in samples which were sent by pneumatic tube comparedto those brought by the courier (18.72±2.70% vs 17.83±2.36%, p=0.007). The electrolyte levels sent by both methods there were nosignificant difference, but the LDH levels were higher in samples sent by pneumatic tube (472.08±100.44 U/L vs 331.25±94.19 U/L,p=0.000). Based on this study, in common can be concluded that the pneumatic tube system does not effect on the routine blood testresults, except on RDW and does not cause changes due to haemolysis (on electrolyte) except the LDH levels elevates. So based on thisstudy, it is recommended to send samples for LDH test only by courier.